PENGARUH KEPEMILIKAN MANAJEMEN, INSTITUSI DAN KELUARGA TERHADAP KEBIJAKAN HUTANG DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Christian Timotius Peilouw; Galuh Budi Astuti (Universitas Katolik Widya Karya Malang, 2021)
This research is an explanatory research, intendingto find the effect of share ownership by management,institutions, and families, on debt policy which use agencytheory, with variables of profitability intervening. The studypopulation is the IDX companies other than banks andfinance, which were registered in the 2015-2016 period. Thesampling technique used purposive sampling so as many as330 companies were obtained. Data analysis technique usedis Partial Least Squares (PLS) by testing the hypothesisstatistically.The result is there is no effect of management ownership onprofitability, there is an influence of management ownershipon debt policy, there is an influence of institutionalownership on profitability, there is no effect of institutionalownership on debt policy, there is no influence of familyownership on profitability, there is no influence of ownershipof family ownership on debt policy , there is an effect ofprofitability on debt policy, there is no effect of managementownership on debt policy through profitability, there is aninfluence of institutional ownership on debt policy throughprofitability, there is no influence of family ownership ondebt policy through profitability.